A Study on the Right of Criminal Procedure Participants to Consent - Dong, Zining (Transactions on Social Science, Education and Humanities Research, 2024)
In the context of China’s emphasis on the pursuit of “protecting human rights” in criminal proceedings, the rights of participants at various stages of litigation have been continuously improved. However, there still exist certain deficiencies regarding the establishment of the right to consent to procedures. At the level of values, the establishment of the right of procedural consent for parties is a full embodiment of the freedom to safeguard human rights, supported by specific legal principles. In current legal texts, the right of procedural consent for parties is reflected to some extent in relevant provisions such as expedited procedures and simplified procedures, with different application modes in different scenarios. Addressing the problems existing in the legislation and practice of the right of procedural consent for parties, it is proposed to improve the current setup and application of the right of procedural consent for parties in criminal proceedings.